Photoinduced CO2 Conversion under Arctic Conditions – The High Potential of Plasmon Chemistry under Low Temperature - Zabelina, Anna; Dedek, Jakub; Guselnikova, Olga; Zabelin, Denis; Trelin, Andrii; Miliutina, Elena; Kolska, Zdenka; Siegel, Jakub; Svorcik, Vaclav; Váňa, Jiří; Lyutakov, Oleksiy (American Chemical Society, 2023)
"The conversion of CO2 to fine chemicals is an efficient tool for reducing the negative impact of human activities on the environment. In this work, we show that CO2 capture and its sunlight-based activation can proceed efficiently even at low, practically arctic temperatures with the implementation of so-called plasmon-assisted chemistry. We propose the specific photocatalyst consisting of two parts: (i) an organic shell responsible for CO2 capture and (ii) a plasmon-active metal nanoparticle core for activation of entrapped CO2 and involving it in the cycloaddition reaction. The effect of temperature on the plasmon-assisted CO2 cycloaddition was studied, and a reaction with only slight temperature sensitivity was observed. Theoretical calculations indicated a significant decrease in the ""apparent"" activation barrier of the reaction under the plasmon-assisted mechanism. Our results open an opportunity for the world economy to exploit the vast Arctic and Antarctic (or close to them) territories where the powerful solar potential is practically not used yet."
Fotoindukovaná konverze CO2 za arktických podmínek – Vysoký potenciál plasmonové chemie za nízké teploty
Keywords: photocatalysis; hybrid catalyst; plasmon-assisted chemistry; CO2 cycloaddition; low temperature; fotokatalýza; hybridní katalyzátor; plasmonem asistovaná chemie; cykloadice CO2; nizká teplota